Beyond prostate-specific antigen: utilizing novel strategies to screen men for prostate cancer. Issue 5 (September 2016) - Loeb, Stacy; Lilja, Hans; Vickers, Andrew
Abstract : Purpose of review: The purpose of this article is to review blood and urine tests that are currently available and under investigation for a role in prostate cancer screening and detection. Recent findings: Compared with total prostate-specific antigen (PSA) alone, its combination with percentage free-to-total PSA contributes greater specificity for prostate cancer, and is a component of two newer blood tests called the 4kScore and Prostate Health Index. All three tests improve the prediction of high-grade disease and are commercially available options to aid in initial or repeat prostate biopsy decisions. PCA3 is a urinary marker that is currently available for repeat prostate biopsy decisions. Although PCA3 alone has inferior prediction of clinically significant disease and requires collection of urine after digital rectal examination, it may be combined with other clinical variables or other urine markers like TMPRSS2:ERG to improve performance. Little data are available to support a role for single nucleotide polymorphisms or other investigational markers in early detection. Summary: Several commercially available blood and urine tests have been shown to improve specificity of PSA for high-grade prostate cancer. Use of such tests would decrease unnecessary biopsy and overdiagnosis of indolent disease. Biopsy of men with moderately elevated PSA without use of such a reflex test should be discouraged.